REKONSTRUKSI TEORI PRODUKSI KONTEMPORER BERBASIS MAQASHID SYARIAH: UPAYA MEWUJUDKAN KESEJAHTERAAN EKONOMI - M. Yusuf Harahap; Yusrizal Yusrizal; Dinda Tazkiyah Harahap; Ayya Azzahra; Rahman Jalaludin Siregar; Iqbal Mustaqim; Mhd. Yahya; Wardah Nasution; Siti Aisyah Br Hsb (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Contemporary production theory is often trapped in the profit maximization paradigm that ignores moral aspects and environmental sustainability. This study aims to reconstruct production theory through the perspective of Maqashid Sharia in realizing holistic economic welfare. This research is descriptive-analytical and normative-conceptual, namely by critically examining conventional production theory and Islamic economics, then reconstructing it based on the Maqashid Sharia framework. The results of the study show that production in the Maqashid Sharia perspective is not only oriented towards material output, but must include protection of five main elements, namely the five main objectives of Islamic law: protecting religion (din), soul (nafs), reason (aql), descendants (nasl), and property (mal). This reconstruction produces a production model oriented towards maslahah, where economic welfare is achieved through a balance between fulfilling material needs and maintaining spiritual and social values